p38MAPK and Chemotherapy: We Always Need to Hear Both Sides of the Story - García-Cano, Jesús; Roche, Olga; Cimas, Francisco J.; Pascual-Serra, Raquel; Ortega-Muelas, Marta; Fernández-Aroca, Diego M.; Sánchez-Prieto, Ricardo (Frontiers in Cell and Developmental Biology, 2016)
The p38MAPK signalling pathway was initially described as a stress response mechanism. In fact, during previous decades, it was considered a pathway with little interest in oncology especially in comparison with other MAPKs such as ERK1/2, known to be target of oncogenes like Ras. However, their involvement in apoptotic cell death phenomena makes this signalling pathway more attractive for many cancer research laboratories. This apoptotic role allows to establish a link between p38MAPK and regular chemotherapeutic agents such as Cisplatin or base analogues (Cytarabine, Gemcitabine or 5-Fluorouracil) which are currently used in hospitals across the world. In fact, and more recently, p38MAPK has also been connected with targeted therapies like tyrosine kinase inhibitors (vg. Imatinib, Sorafenib) and, to a lesser extent, with monoclonal antibodies. In addition, the oncogenic or tumour suppressor potential of this signalling pathway has aroused the interest of the scientific community in evaluating p38MAPK as a novel target for cancer therapy. In this review, we will summarize the role of p38MAPK in chemotherapy as well as the potential that p38MAPK inhibition can bring to cancer therapy. All the evidences suggest that p38MAPK could be a double-edged sword and that the search for the most appropriate candidate patients depending on their pathology and treatment will lead to a more rational use of this new therapeutic tool.